THE IMPACT OF COMMUNITY ACTIVITIES ON TRANSPORT IN THE DOWNTOWN AREA OF TOMOHON IN THE NEW NORMAL ERA - Thanos, Samitha A. R.; -, Sangkertadi; Timboeleng, James A (SPASIAL, 2021)
Society cannot be separated from activities in order to meet important needs. Activities to meet this need require a tool for moving places, namely modes of transportation. Movements of transportation modes must be well planned so that people can feel safe and comfortable. Since the city center of Tomohon is a diverse land use area, activities to meet the needs of the area are concentrated. This has generated interest in conducting research on the impact of community activities on transportation, especially in the context of the COVID-19 pandemic. This study aims to identify the characteristics and patterns of community activity, the factors that influence it, the extent and model of Tomohon's downtown traffic impact in the new normal era. This study uses a quantitative approach using methods of factor analysis and path analysis. The sample for this survey consisted of 400 respondents randomly selected from a target audience of people active in downtown Tomohon. The results of this survey are (1) the characteristics and patterns of community activities based on the main forms of activities carried out, the timing of activities, and the types of activities. (2) There are three community activity factors that influence before the new normal era, and there are two community activity factors that influence during the new normal era. (3) Social activity factors (F3) have the greatest impact on the traffic attraction before the new normal era, while economic, educational and religious activity factors (K1) have the greatest influence on traffic attraction during the new normal era. Keywords: factors, community activities, traffic, path analysis